Processo de criação de municípios: análise a partir de indicadores de viabilidade econômico-financeira em Santa Bárbara do Pará - LIMA, Ailton Pires de (Universidade Federal do Pará, 2018)
Currently, various localities throughout Brazil are working to become cities, but since 1996 the Law 15/96 suspended the process of emancipation which had been resumed with the 1988 Constitution. The new constitution allowed the legislatures the power to regulate the Act and establish minimum rules of feasibility for the creation of a new municipality .As this period there was an outbreak of emancipating the federal government through the Congress passed a constitutional amendment, which, returning to the Congress itself the prerogative to regulate the field, as well as to determine rules for the preparation of the Feasibility Study. In 2008 the Senate approved a proposed regulation of Law and has submitted the attached rules for the preparation of Feasibility Studies which includes the financial economic, Political and Administrative Feasibility Feasibility and Socio-Environmental Urban. Thus, the purpose of this study is to analyze economic and financial situation of the City of Santa Barbara, in the period 2004 to 2009 and demonstrate the economic and financial situation of this Municipality during the period analyzed, showing the positive and negative factors occurring in these exercises and making sure the city, which was installed in 1993, fits the requirements of current law also had with reference to the data analysis of the HDI, tracing a parallel between the financial results and quality of life for citizens of Santa Barbara Pará Through documentary research on balance budgets, financial data are extracted and applies to quotients to obtain the results, evaluated in this study. This work was carried out through a descriptive research with a quantitative and qualitative approach. In the analysis of financial data it appears that the economic and financial situation the City could hardly be emancipated today.